'I See the Struggle against Race Supremacy and Racial Inequality as World-Wide': Anti-Apartheid Campaigns, Civil Rights Struggles, and the 1961 Track and Field Tours of South Africa. Issue 8 (15th July 2022) - Dyreson, Mark; Sikes, Michelle M.
ABSTRACT: As the Civil Rights Movement in the US reached its apogee and apartheid in South Africa cemented its grip, the American Amateur Athletic Union in 1961 announced plans to send a team of athletics all-stars to the African nation. Following tours of South Africa by all-white American teams in 1931 and 1950, as well as a 1938 tour scuttled by racial disagreements, the 1961 proposal drew fire from Civil Rights leaders and anti-apartheid activists. In the early 1960s these two factions of fighters for racial justice through sport made common cause. Jack Roosevelt Robinson, the iconic leader of the crusade to desegregate American baseball, joined the anti-apartheid crusade and proposed a sporting boycott of South Africa. Robinson also lobbied Black athletes to boycott track meets that did not extend interracial inclusion to the stadium stands and local accommodations. Under pressure, the Amateur Athletic Union abandoned its 1961 tour, but the US Department of State sent a small, entirely white contingent of athletes to the apartheid state on a 'goodwill' mission. The 1961 incidents in the US and South Africa highlighted the growing intersection of racial justice crusades centred on sport that targeted both American segregation and South African apartheid.